Righteous Philosophy in Glorious Qur’an (An interpretation balanced study) - بركاوي جليب دارم ا.م. د. (lark, 2021)
Taqiyya is a rational and innate principle that results in many gains in preserving souls, safeguarding sanctities and protecting religion. It is not a means of submission and surrender or a call for weakness and defeat. Islam is greater to allow such a thing. This doctrine has been widely admired by the pioneers of Islamic thought, which It gained its importance from the frequent revelation of the Revelation and the tightening of the Sunnah, and it is not permissible in any case, but it is forbidden to resort to it if it requires the work of corruption of religion or a violation of the creation or bloodshed, and the difference of some Muslim scholars on it is only a verbal dispute. Some of them discussed of its theory under the name of coercion, and some of them called it Taqiyya. The disobedience and curtailment of the Shiites of Imami for their use of it, lacking its ingredients